SOROTAN GERAKAN PENTERJEMAHAN DAN PENERBITAN BUKU-BUKU DALAM DAWLAH ’ABBASIYYAH DI BAGHDAD- SATU ANALISA IKTIBAR DARI SUDUT INSTITUSI PENERBITAN SEMASA - Berahim@Ibrahim, Ahmad Zaki; Hamzah, Norhayati (Journal of Al-Tamaddun, 2008)
The early period of Islam witnessed the glory of knowledge especially during the ’Abbasid Caliphate. This was due to the establishment of Bait al-Hikmah by Harun al-Rashid ( A.H.170-193/ A.D. 786-808), the fifth caliph that led to the development of translation movement and publication. Bait al-Hikmah that functioned as a library and a translation centre in Baghdad had played a vital role in the growth and development of knowledge among the Muslims and non-Muslims at that time. This article will discuss the early history of translation movement in Islam starting from the period of the Umayyad Caliphate till the reign of al-Ma’mun (A.H. 198-218 / A.D. 813-833), the son of Harun al-Rashid and the sixth ’Abbasid Caliph. The achievement of Bait al-Hikmah and its influence on intellectual movement will be discussed in detail as well as the lessons from the achievement of Bait al-Hikmah that could be taken by contemporary translation and publication institutions.